Large-Scale Self-Assembly of anisotropic graphene oxide films via blade Coating: Sustainable design and Stimuli-Responsive performance for biomimicry - Musen Chen; Qian Wang; Maxim Trubyanov; Kou Yang; Aleksandr S. Aglikov; Ge Qi; Ekaterina V. Skorb; Kostya S. Novoselov; Daria V. Andreeva (Materials & Design, 2023)
Sustainable structural design, utilizing material to imitate natural biological systems, presents both promise and challenges. By avoiding interfacial problems encountered in composite counterparts, such designs offer self-adaptive materials for smart housing and green architecture, etc. In this study, we demonstrate the feasibility of large-scale self-assembly of graphene oxide (GO) flakes into anisotropic films through a simple blade coating technique. Through the application of blade coating to a highly concentrated nematic GO suspension, we successfully fabricate GO films with morphological gradient and patterning. Additionally, we propose a statistical analysis method utilizing scanning electron microscopy (SEM) images for the characterization of materials with macroscopic surface morphology. Furthermore, we explore the application of these GO films as low-dimensional soft actuators, revealing their outstanding stimuli-responsive performance and self-adaptation to environment. Such robust and flexible films can be used as integral building elements in the bioinspired design of sustainable smart housing facilitating remote robotization and sensing capabilities.